No ntuberculous Mycobacteria - M. V. Makarova; L. D. Guntupova (Биопрепараты: Профилактика, диагностика, лечение)
There has been a sharp increase in the number of diseases associated with potentially pathogenic microorganisms of the genus Mycobacterium, which differ from Mycobacterium tuberculosis. These bacteria are known as atypical mycobacteria or nontuberculosis mycobacteria (NTM), and the diseases they cause are called mycobacteriosis. NTMs include more than 20 species of acid-resistant microorganisms that are widespread in the environment and that are not members of the M. tuberculosis complex. However, the role of certain types of NTMs in the pathogenesis of human diseases is rather ambiguous. The aim of the paper was to analyse the current rise in the incidence of NTM diseases, as well as the main areas of research on early diagnosis of mycobacteriosis and the detection and testing of drug susceptibility of these microorganisms. The paper summarises current views on NTM species differences, their prevalence and pathogenicity for humans and animals. The authors analysed the main efforts aimed at diagnosis and treatment of NTM diseases. The paper cites the results of the study of NTM susceptibility/resistance to anti-tuberculosis drugs. The diagnosis of mycobacteriosis remains extremely difficult, mainly because of the similarity of the clinico-radiological evidence with that of tuberculosis. Detection of NTM multiple and extensive drug resistance to the majority of anti-tuberculosis drugs complicates the treatment of the NTM disease. Further study of various aspects of NTM diseases is especially important given the increase in the incidence and prevalence of mycobacteriosis all over the world, challenging differential diagnosis, and detection of NTM extensive drug resistance.